2018
DOI: 10.1186/s13041-018-0351-1
|View full text |Cite
|
Sign up to set email alerts
|

Resolvin D2 protects against cerebral ischemia/reperfusion injury in rats

Abstract: Cerebral ischemia/reperfusion (I/R) injury is a critical factor leading to a poor prognosis for ischemic stroke patients. ω-3 fatty acid supplements taken as part of a daily diet have been shown to improve the prognosis of patients with ischemic stroke. In this study, we aimed to investigate the potential effects of resolvin D2 (RvD2), a derivative of ω-3 fatty acids, and its possible advantage on cerebral I/R injury in rats. Cerebral I/R caused by middle cerebral artery occlusion and reperfusion (MCAO/R) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 37 publications
(36 reference statements)
2
61
0
Order By: Relevance
“…These results reveal that adding to the pro-resolving effect of DRV2/GPR18 on immune cells, the receptor participates in the healing of tissues through the activation of the Gαi protein in endothelial cells. In a rat model of cerebral ischemia/reperfusion injury, Zuo et al (2018) observed that the middle cerebral artery occlusion and reperfusion stimulus led to a significant decreased in RvD2 production and DRV2/GPR18 expression. Exogenous administration of RvD2 reversed the effect especially on neurons and brain microvascular endothelial cells ( Zuo et al, 2018 ).…”
Section: Drv2/gpr18mentioning
confidence: 98%
See 2 more Smart Citations
“…These results reveal that adding to the pro-resolving effect of DRV2/GPR18 on immune cells, the receptor participates in the healing of tissues through the activation of the Gαi protein in endothelial cells. In a rat model of cerebral ischemia/reperfusion injury, Zuo et al (2018) observed that the middle cerebral artery occlusion and reperfusion stimulus led to a significant decreased in RvD2 production and DRV2/GPR18 expression. Exogenous administration of RvD2 reversed the effect especially on neurons and brain microvascular endothelial cells ( Zuo et al, 2018 ).…”
Section: Drv2/gpr18mentioning
confidence: 98%
“…In a rat model of cerebral ischemia/reperfusion injury, Zuo et al (2018) observed that the middle cerebral artery occlusion and reperfusion stimulus led to a significant decreased in RvD2 production and DRV2/GPR18 expression. Exogenous administration of RvD2 reversed the effect especially on neurons and brain microvascular endothelial cells ( Zuo et al, 2018 ). These effects were partly mediated by increased ERK1/2 phosphorylation and the increased production of neuronal NOS (nNOS) and endothelial NOS (eNOS).…”
Section: Drv2/gpr18mentioning
confidence: 98%
See 1 more Smart Citation
“…They induce remote functional recovery after brain damage (Bisicchia et al, 2018). Resolvin D2 and aspirin‐triggered resolvin D2 protect from cerebral ischemic injury through ERK1/2 phosphorylation followed by stimulation of nNOS or eNOS to inhibit programmed neuronal cell death and increase zonula occludens‐1 for the maintenance of blood‐brain barrier integrity (Zuo et al, 2018). Resolvin D3, resolvin D5, aspirin‐triggered resolvin D3, and aspirin‐triggered resolvin D5 halt neuroinflammatory process (Dalli et al, 2013; Hong et al, 2005).…”
Section: Roles Of Dha and Its Metabolites In Brain Functionmentioning
confidence: 99%
“…The activation of the DRV2/GRP18 axis has been reported to reduce neutrophil infiltration in a mouse model of hind limb ischemia/reperfusion [26]. In a mouse model of cerebral ischemia/reperfusion injury, exogenous administration of RvD2 reduced infarction area, inflammatory response, and brain edema [27]. In kidney ischemia/reperfusion injury, RvD1 administration reduced infiltrating leukocytes and preserved glomerular function [28].…”
Section: Proresolving Pathways Of E-series and D-series Resolvinsmentioning
confidence: 99%